2015
DOI: 10.1016/j.marpolbul.2015.06.035
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metals in surface sediments of the intertidal Laizhou Bay, Bohai Sea, China: Distributions, sources and contamination assessment

Abstract: a b s t r a c tSurface sediments from the intertidal zone of the southwestern Laizhou Bay were analyzed for heavy metals to seek their concentrations, distributions, pollution status, potential ecological risks and possible sources. The concentrations of As, Cd, Cr, Cu, Hg, Ni, Pb and Zn were in the ranges of 4. 65-9.65, 0.11-0.28, 25.85-42.75, 7.57-21.29, 0.022-0.054, 12.85-25.35, 9.65-17.65 and 38.22-73.81 lg g À1 dry sediment weight, respectively. Cd and Hg presented a status of no pollution to moderate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(16 citation statements)
references
References 45 publications
(41 reference statements)
1
15
0
Order By: Relevance
“…The Monte Carlo simulation demonstrated that only Hg in September 2016 showed a probability (0.03%) of moderate risk (Table 6). The sources of Hg in this area were mainly land-based human activities, including factory discharge and combustion of fossil fuels, and river transportation is possibly the main means by which Hg enters Laizhou Bay [12, 14].…”
Section: Resultsmentioning
confidence: 99%
“…The Monte Carlo simulation demonstrated that only Hg in September 2016 showed a probability (0.03%) of moderate risk (Table 6). The sources of Hg in this area were mainly land-based human activities, including factory discharge and combustion of fossil fuels, and river transportation is possibly the main means by which Hg enters Laizhou Bay [12, 14].…”
Section: Resultsmentioning
confidence: 99%
“…In addition to hydrological factors, the particle size and components of sediments affect metal concentrations. In particular, finer particles tend to be metal adsorbent, and this tends to affect the physical transportation of metals [ 22 ]. Fine particles are also always associated with organic matter, as observed in the current study, and this resulted in metal deposition, especially within the wetland sites from which metals were slowly being released downstream [ 40 , 41 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, improved insights into mechanisms of accumulation and geochemical distributions of metals are extremely important to gauge the extent of metal pollution in aquatic systems [ 3 , 12 , 21 ]. In turn, this monitoring is crucial when assessing ecological risks and developing pollution control strategies [ 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Heavy metals (HMs) are extremely poisonous, non-biodegradable, and readily accumulated in the aquatic life. Surface runoff, especially with the development of industry, agriculture, and urbanization, discharged them into the marine environment (Diagomanolin et al, 2004;Zhang & Gao, 2015;Ranjbar Jafarabadi et al, 2017;Liu et al, 2018;Younis et al, 2019;Soliman et al, 2020). Metals are scavenged by particulate matter and deposited to coastal sediments after entering coastal waters, and hence, sediments are considered a major component of metal storage in marine ecosystems (Pan & Wang, 2012).…”
Section: Introductionmentioning
confidence: 99%